PERFORMANCE APPRAISAL PRACTICES AND PERFORMANCE OF COMMERCIAL BANKS IN MACHAKOS COUNTY - KENYA - MWANTHI, WINFRED M. (My University, 2019)
This study investigated how performance appraisal practices affect performance of commercial banks in Machakos County. The specific objectives were to: establish how preparation for performance appraisal influences performance of commercial banks in Machakos County, determining how conducting of performance appraisal affects performance of commercial banks in Machakos County and establish how feedback on performance appraisal affects performance of commercial banks in Machakos County. The study adopted a descriptive research design to collect both qualitative and quantitative data. The target population for this study was three hundred and eighty (380) employees of 16 commercial banks in the county. Stratified random sampling technique was used. Sample size for the study was one hundred and ninety-five (195) respondents. Questionnaires and interview guide were used to collect both quantitative and qualitative data. Data analysis was done using the Statistical Package for Social Science (SPSS) and MS Excel. Inferential statistics, that is, regression and the Pearson Correlation Coefficient was used to test for the relationship between the independent variables and the dependent variable. Multiple regression analysis indicated that there is a significant positive relationship between preparation of performance appraisal and performance of commercial banks in Machakos County indicated by a t-ratio of 1.467. The study found positive relationship between performance of commercial banks in Machakos County and conducting performance appraisal with a statistically significant coefficient as indicated by a t-ratio of 1.226 and a positive relationship between performance of commercial banks in Machakos County and feedback on performance appraisal with a statistically significant coefficient as indicated by a t-ratio of 1.444. From the findings, the study recommends that organizations should prepare well before conducting the employee performance appraisal. Employees should be well trained and involved in setting personal and company goals. The study also recommends that PA should also be used as a basis for making development and improvement plans and reaching agreement about what should be done in the future to enhance the bank’s effectiveness.